Eucommia ulmoides seed oil is a complementary food for suppressing digestive tumors - Wu, Jinzheng; Wen, Liang; Karthick Rajan, Durairaj; Liu, Yan; Yang, Xin; Jiang, Hao; Yan, Jinhua; Shu, Bo; Zhang, Shubing (Frontiers in Pharmacology, 2025)
BackgroundNatural products and their bioactive components serve as valuable resources for anticancer drug discovery. Eucommia ulmoides, a medicinal and edible plant widely used in traditional medicine, contains functionally significant compounds in its seeds, particularly Eucommia ulmoides seed oil (EUSO). Previous studies have demonstrated EUSO’s promising preventive and therapeutic potential against metabolic disorders, including hypertension, diabetes, and obesity. However, its therapeutic effects on malignancies, particularly digestive system cancers, remain unexplored.MethodsTo evaluate the antitumor effects of EUSO, we performed in vitro and in vivo functional analyses using Cell viability, clone formation, migration capacities, and apoptosis rates were assessed through CCK-8 assays, colony formation assays, Transwell assays, and flow cytometry in hepatocellular carcinoma (HCC) and pancreatic cancer cell models. In vivo antitumor efficacy was further validated using subcutaneous xenograft models in nude mice. Mechanistically, transcriptomic profiling (RNA-seq) and Western blotting were conducted to identify EUSO-regulated signaling pathways.ResultsEUSO exhibited dose-dependent suppression of HCC and pancreatic cancer cell proliferation, colony formation, and migration. Flow cytometry confirmed EUSO-induced apoptosis. In vivo, EUSO administration suppressed tumor growth in xenograft models. Mechanistic studies revealed that EUSO downregulated PI3K-AKT-mTOR pathway activation, evidenced by reduced phosphorylation of AKT (Ser473) and mTOR (Ser2448).ConclusionEUSO attenuates the malignant progression of digestive system cancers by inhibiting the PI3K-AKT-mTOR pathway. These results provide mechanistic evidence supporting the potential application of EUSO as an adjuvant therapeutic agent in cancer management and warrant further clinical investigation into its chemopreventive and complementary therapeutic value.